2018
DOI: 10.1519/jsc.0000000000002341
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Near-Infrared Spectroscopy for Measuring Intermittent Handgrip Contractions in Sport Climbers

Abstract: Baláš, J, Kodejška, J, Krupková, D, Hannsmann, J, and Fryer, S. Reliability of near-infrared spectroscopy for measuring intermittent handgrip contractions in sport climbers. J Strength Cond Res 32(2): 494-501, 2018-The use of near-infrared spectroscopy (NIRS) to investigate muscle oxygenation changes during physical tasks such as rock climbing has rapidly increased within recent years; yet, there is no known measure of reliability. The current study aimed to determine intersession reliability and minimal detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
(45 reference statements)
2
26
2
Order By: Relevance
“…Differences in the haemodynamic response between the 1st and 2nd recovery show that muscle temperature, rather than hydrostatic pressure, are responsible for TSI changes. However, the differences in tHb and TSI between PAS and CWI recovery strategies were small and did not exceed the minimal detectable changes stated for this type of measurement [1].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Differences in the haemodynamic response between the 1st and 2nd recovery show that muscle temperature, rather than hydrostatic pressure, are responsible for TSI changes. However, the differences in tHb and TSI between PAS and CWI recovery strategies were small and did not exceed the minimal detectable changes stated for this type of measurement [1].…”
Section: Discussionmentioning
confidence: 61%
“…Effect size for ANOVA was calculated using partial eta squared (µ p 2 ). Mean detectable change, as stated previously [1], was taken for a criterion of practical effect. All calculations were completed using IBM SPPS 24.0 (IBM, Armonk, New York).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, a plethora of studies have demonstrated the diagnostic qualities of NIRS, from threshold testing 34,35 , muscle damage analysis 36 and high intensity interval response 37,38 . Similar physiological reasoning has been applied to NIRS measurements during sport climbing, highlighting the importance of specific NIRS derived parameters 17 . SmO 2 min as an indicator of muscle oxidative capacity and a predictor of performance for climbing specifically is discussed by both Balas et al 12 and Fryer et al 13 .…”
Section: Discussionmentioning
confidence: 92%
“…The hand position applied by all participants was a half crimp; the thumb was not used. A 23 mm rung depth was used for all the trails, following the procedure of a series of previous publication 17,24 . For every trial the participants were allowed to apply commercially available climbing chalk (magnesium carbonate).…”
Section: Finger-hang Testmentioning
confidence: 99%
See 1 more Smart Citation